P360 Improving health care worker understanding of LGBTQ+ patients through storytelling and empathy. (14th July 2019) - Long, Amanda; Fields, Errol; Chandran, Aruna; Bademosi, Kehinde; Sawyer, Simone; Murray, Jeannie; Schumacher, Christina; Greenbaum, Adena; Jennings, Jacky
Abstract : Background: Significant HIV disparities affect LGBTQ+ populations and medical mistrust from experiences of healthcare worker (HCW) stigma is a key barrier to HIV prevention and care. This stigma results from many factors, including lack of HCW understanding of LGBTQ+ experiences. The goal was to determine if storytelling nights, events where LGBTQ+ persons share in-depth, personal accounts of their experiences, increased HCW understanding of LGBTQ+ patients. Methods: The study design was a retrospective post-test design with surveys conducted after each of 5 storytelling nights and qualitative data collected via post-it notes during each event. All city residents were encouraged to attend, with marketing focused on the LGBTQ+ community and HCWs that interact with LGBTQ+ patients. The survey measured changes in HCW understanding of LGBTQ+ patients as a result of the event. Post-it notes measured HCW reactions to LGBTQ+ patient experiences shared through the storytelling and were analyzed using thematic analysis. Results: 416 individuals attended the storytelling nights (mean 83, SD 12.7 per event) and 56 HCWs completed a survey. 49 (87.5%) strongly agreed or agreed that they could better understand their patients' feelings and concerns after the event. 449 post-its (mean 90, SD 23.1 per event) were collected and 43 (9.6%) post-its were directly related to HCW reflections on LGBTQ+ patients. Three themes emerged from post-it responses: learning new approaches for working with LGBTQ+ patients through the stories; storytelling nights meeting an educational need for HCWs working with LGBTQ+ patients; and the realization that HCWs should take more time to learn about each patient's needs. Conclusion: Events that encourage sharing of experiences, such as storytelling nights, may serve as an effective tool for increasing understanding by HCWs of LGBTQ+ patients by the sharing of unique experiences of LGBTQ+ persons. This may ultimately help to decrease medical distrust of LGBTQ+ populations and improve sexual health and well-being. Disclosure: No significant relationships.